When Corporations Break the Law
This flyer argues that widespread corporate crime—citing major companies accused of bribery, slush funds, and other illegal activities—ultimately costs consumers through higher prices and weak penalties. It claims that fines imposed on corporations are too small to deter misconduct and highlights estimates that white-collar crime costs Americans billions annually. The document urges support for a New York State Democratic Committee resolution calling for a full-scale congressional investigation into corporate power.